2005
DOI: 10.1071/fp05005
|View full text |Cite
|
Sign up to set email alerts
|

Topsoil foraging and phosphorus acquisition efficiency in maize (Zea mays)

Abstract: In soybean and common bean, enhanced topsoil foraging permitted by shallow root architectures is advantageous for phosphorus acquisition from stratified soils. The importance of this phenomenon in graminaceous crops, which have different root architecture and morphology from legumes, is unclear. In this study we evaluated the importance of shallow roots for phosphorus acquisition in maize (Zea mays L.). In a field study, maize genotypes with shallower roots had greater growth in low phosphorus soil than deep-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
141
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(154 citation statements)
references
References 61 publications
6
141
1
6
Order By: Relevance
“…Cosegregation of QTL controlling a phene with phosphorus acquisition is strong evidence that the phene is important for phosphorus acquisition in a range of phenotypes. Analysis of maize and bean RILs varying in RGA shows that this phene has a dominant influence on phosphorus acquisition, accounting for up to 6-fold variation in phosphorus acquisition and 3-fold variation in yield of bean in low-phosphorus soil (Lynch and Brown, 2001), and 2-fold variation in phosphorus acquisition in maize (Zhu et al, 2005b). QTL associated with RGA in bean cosegregate with yield under phosphorus stress .…”
Section: Shallower Root Growth Anglementioning
confidence: 99%
“…Cosegregation of QTL controlling a phene with phosphorus acquisition is strong evidence that the phene is important for phosphorus acquisition in a range of phenotypes. Analysis of maize and bean RILs varying in RGA shows that this phene has a dominant influence on phosphorus acquisition, accounting for up to 6-fold variation in phosphorus acquisition and 3-fold variation in yield of bean in low-phosphorus soil (Lynch and Brown, 2001), and 2-fold variation in phosphorus acquisition in maize (Zhu et al, 2005b). QTL associated with RGA in bean cosegregate with yield under phosphorus stress .…”
Section: Shallower Root Growth Anglementioning
confidence: 99%
“…When grown under limited phosphorus (P) availability, roots exhibit a shallower architecture that results from the inhibition of PR elongation and the concomitant increase in LR formation (Williamson et al, 2001;LĂłpez-Bucio et al, 2002;Sanchez-Calderon et al, 2005). Such an architectural rearrangement of the root is thought to improve the plant's ability to forage P from the usually P-enriched topsoil horizon (Lynch and Brown, 2001;Rubio et al, 2003;Zhu et al, 2005). In contrast to low P, reduced nitrogen (N) availability stimulates PR and particularly LR elongation but not LR initiation (Linkohr et al, 2002;LĂłpez-Bucio et al, 2003).…”
mentioning
confidence: 99%
“…Previous studies have shown that external factors can affect root morphology and architecture and that root systems have an innate ability to respond and adapt to their rooting environment (Malamy, 2005). Additionally, many reports indicate that certain root qualities in crop plants can help enhance productivity in resource-limited environments due to improved nutrient and water scavenging abilities (Liao et al, 2001;Zhu et al, 2005;Ribaut et al, 2009). Identifying, evaluating, and selectively introducing both intrinsic and environmentally responsive root architectural characteristics into breeding programs may be a promising area for improving crop production on resource-limited agricultural systems (de Dorlodot et al, 2007).…”
mentioning
confidence: 99%